2011
DOI: 10.1074/jbc.m110.176479
|View full text |Cite
|
Sign up to set email alerts
|

Premature Ligand-Receptor Interaction during Biosynthesis Limits the Production of Growth Factor Midkine and Its Receptor LDL Receptor-related Protein 1

Abstract: Protein production within the secretory pathway is accomplished by complex but organized processes. Here, we demonstrate that the growth factor midkine interacts with LDL receptor-related protein 1 (LRP1) at high affinity (K d value, 2.7 nM) not only at the cell surface but also within the secretory pathway during biosynthesis. The latter premature ligand-receptor interaction resulted in aggregate formation and consequently suppressed midkine secretion and LRP1 maturation. We utilized an endoplasmic reticulum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…As a mechanism of evasion of the immune response by tumors, preceding immuno-editing, we hypothesize that tumors may over-express RAP, or other as yet identified endogenous CD91 inhibitors, to impair antigen transfer. A previous study showed a correlation between elevated RAP levels and progressive disease in colon cancer patients (36). We expect this mechanism to occur during tumor initiation because antigen burden is very low, and HSP-mediated antigen uptake prevails, and allows the tumor to be firmly established.…”
Section: Discussionmentioning
confidence: 92%
“…As a mechanism of evasion of the immune response by tumors, preceding immuno-editing, we hypothesize that tumors may over-express RAP, or other as yet identified endogenous CD91 inhibitors, to impair antigen transfer. A previous study showed a correlation between elevated RAP levels and progressive disease in colon cancer patients (36). We expect this mechanism to occur during tumor initiation because antigen burden is very low, and HSP-mediated antigen uptake prevails, and allows the tumor to be firmly established.…”
Section: Discussionmentioning
confidence: 92%
“…S1). Notch2 (34,35), LRP1 (36)(37)(38), PTPz (39), and integrins (a4, a6, b1; ref. 40) are candidates for midkine receptors, and they were similarly expressed in both wild-type and MYCN transgenic mice.…”
Section: Resultsmentioning
confidence: 99%
“…Matsui and coworkers found two trifluoro compounds: one (PubChem 4603792) is 2-(2,6-dimethylpiperidin-1-yl)-4-thiophen-2-yl-6-(trifluoromethy)pyrimidine, and the other has a related structure that inhibits MDK effectively without cytotoxic effects at osteoblast-like cells not at cancer cells (Matsui et al, 2010). Last report by Sakamoto and coworkers in 2011 showed that the premature ligandreceptor interaction during biosynthesis limits the production of MDK and its receptor LDL receptor-related protein 1 (LRP1) (Sakamoto et al,2011). They utilized an endoplasmic reticulum (ER)-retrieval signal and a LRP1 fragment, which strongly bound to midkine and the LRP1-specialized chaperone RAP, to construct an ER-trapper.…”
Section: Midkine Inhibitorsmentioning
confidence: 99%